Doing business 2007 : how to reform : comparing regulation in 175 economies. - Djankov, Simeon; McLiesh, Caralee; Klein, Michael (Michael U.) (Doing Business ;, 2006)
Doing Business 2007 focuses on reforms, identifies top reformers in business regulation, and best practices in how to reform. This volume is the fourth in a series of annual reports investigating global regulations that enhance business activity and those that constrain it. Co-sponsored by the World Bank and the International Finance Corporation - the private sector arm of the World Bank Group - this year's report measures quantitative indicators on business regulations and their enforcement compared across 175 countries - from Afghanistan to Zimbabwe - and over time. Doing Business 2007 updat.